Desenvolvimento de um modelo de diagnóstico para práticas ESG - Quadros, Vanessa Feijo (2025)
The growing demand for sustainable business practices has driven the adoption of ESG (Environmental, Social, and Governance) criteria as strategic components of organizational management. In this context, the present research proposed the development of a procedural model for auditing ESG practices, applied to a freight transportation company in the road transport sector. This is an applied study with a mixed-methods approach, combining qualitative methods, such as interviews, direct observation, and document analysis with quantitative analysis through the PROMETHEE-ROC technique, aiming to establish a structured prioritization of sustainability-oriented actions. Ten strategic alternatives were analyzed based on six ESG criteria, with their respective weights determined using the Rank Order Centroid technique. The results highlighted the highest priority for actions focused on reducing atmospheric emissions and improving energy efficiency, both with a net flow of ϕ = 0.2919. Next in priority was the development of sustainability reports (ϕ = 0.1756). Lower-priority initiatives included the creation of an Ethics Committee (ϕ = -0.2899) and solid waste management (ϕ = -0.2334). The resulting modelo was structured around four integrated dimensions: Governance and Social Responsibility; Workplace and Human Capital; Environmental Management; and Sustainable Growth and Innovation. The practical application of the model demonstrated that the PROMETHEE-ROC technique is an effective tool to support strategic decision-making and can be replicated in other companies within the logistics sector.